Economic considerations on transfusion medicine and patient blood management - Hofmann, Axel; Ozawa, S.; Farrugia, A.; Farmer, Shannon; Shander, A. (Elsevier, 2013)
In times of escalating health-care cost, it is of great importance tocarefully assess the cost-effectiveness and appropriateness of themost resource-consuming health interventions. A long-standingand common clinical practice that has been underestimated incost and overestimated in effectiveness is the transfusion of allogeneicblood products. Studies show that this intervention comeswith largely underestimated service cost and unacceptably highutilisation variability for matched patients, thus adding billions ofunnecessary dollars to the health-care expenditure each year.Moreover, a large and increasing body of literature points to adose-dependent increase of morbidity and mortality and adverselong-term outcomes associated with transfusion whereas publishedevidence for benefit is extremely limited. This means that transfusion may be a generator for increased hospital stay andpossible re-admissions, resulting in additional billions in unnecessaryexpenditure for the health system. In contrast to this, thereare evidence-based and cost-effective treatment options availableto pre-empt and reduce allogeneic transfusions. The patientspecificrather than a product-centred application of these multiplemodalities is termed patient blood management (PBM). From ahealth-economic perspective, the expeditious implementation ofPBM programmes is clearly indicated. Both patients and payerscould benefit from this concept that has recently been endorsedthrough the World Health Assembly resolution WHA63.12.